Grassland biodiversity restoration increases resistance of carbon fluxes to drought. Issue 7 (14th May 2019) - Cole, Andrew J.; Griffiths, Robert I.; Ward, Susan E.; Whitaker, Jeanette; Ostle, Nicholas J.; Bardgett, Richard D.
Abstract: Evidence suggests that the restoration of plant diversity in grasslands not only brings benefits for biodiversity conservation, but also the delivery of ecosystem services. While biodiversity‐function experiments show that greater plant diversity increases resistance of plant productivity to climate extremes, it is not known whether real‐world management options for grassland restoration likewise stabilize ecosystem responses to extreme climate events. We used a long‐term (23 year) field experiment in northern England to test the hypothesis that management aimed at biodiversity restoration increases the resistance and recovery of ecosystem carbon (C) fluxes to short‐term summer drought. This was tested by measuring plant, soil and microbial responses to a simulated drought in experimental grassland plots where fertilizer application and seed addition have been managed to enhance plant species diversity. The cessation of fertilizer application brought about small increases in plant species richness. Additionally, cessation of fertilizer application reduced overall plant productivity and promoted hemi‐parasitic plants at the expense of grasses and forbs. Resistance of CO2 fluxes to drought, measured as ecosystem respiration, was greater in non‐fertilized plots, as lower plant biomass reduced water demand, likely aided by proportionally more hemi‐parasitic plants further reducing plant biomass. Additionally, legumes increased under drought, thereby contributing to overall resistance of plant productivity. Recovery of soil microbial C and nitrogen was more rapid after rewetting than soil microbial community composition, irrespective of restoration treatment, suggesting high resilience of soil microbial communities to drought. Synthesis and applications . This study shows that while grassland diversity restoration management increases the resistance of carbon fluxes to drought, it also reduces agricultural yields, revealing a trade‐off for land managers. Furthermore legumes, promoted through long‐term restoration treatments, can help to maintain plant community productivity under drought by increasing their biomass. As such, grassland management strategies not only have consequences for ecosystem processes, but also the capacity to withstand extreme weather events. Abstract : This study shows that while grassland diversity restoration management increases the resistance of carbon fluxes to drought, it also reduces agricultural yields, revealing a trade‐off for land managers. Furthermore legumes, promoted through long‐term restoration treatments, can help to maintain plant community productivity under drought by increasing their biomass. As such, grassland management strategies not only have consequences for ecosystem processes, but also the capacity to withstand extreme weather events.